MENINGKATKAN HASIL BELAJAR IPA MELALUI METODE DEMONSTRASI - Nur, Iriani (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2019)
Learning in SD Negeri Seuneubok Pidie, East Aceh Regency, especially class V on science subjects about material for breathing instruments in humans and animals, mastery of material is still very low or has not been successful. Of the 21 students, only 5 students (24%) achieved the Minimum Completion Criteria (KKM) which was set at 6.5 with an average score of 57.4. To overcome the above problems, the steps that need to be implemented are using the Demonstration Method. In its application, the researcher tried on the science subject about the concept of "Respiratory Tools in Humans and Animals".The subjects in this study were 21 students consisting of 14 men and 7 women. To achieve the results in accordance with what the researcher expects, the researchers implement them with II (two) cycles. Each cycle is 2 (two) meetings for 3 (three) months. The results of the description analysis revealed, in the first (first) cycle the average score of students was 66.4 and learning completeness reached 62%, while in the second cycle (second) the average score of students was 78 and learning completeness reached 86%. The conclusion of this study is to use the Demonstration Method in science lessons about the material Respiratory Tools in Humans and Animals can improve the learning outcomes